Ultrasound evaluation of acute pelvic pain in non-pregnant reproductive age females - Basnet, Prabhat; Chhetri, Pramod Kumar (Journal of Chitwan Medical College, 2021)
Background: Ultrasound is one of the best tools for the scanning of the female pelvis. It is easy to operate and very helpful in acute condition to rule out different lower abdominal pathology. Ultimately fast and accurate diagnosis of the pathology by ultrasound is key to further management and treatment. The aim of preset study was to find the common causes of the acute pelvic pain in the non-pregnant reproductive age females. Methods: The study was conducted in Department of Radiology and Imaging of college of medical sciences. Patients with acute pelvic pain of reproductive age non-pregnant female are included in our study. All ultrasound examinations were performed using Toshiba Aplio 500. A prospective cross-sectional study was conducted on 48 patients in college of medical science, Bharatpur, over the period of one year (November 2018 to October 2019). Data obtained were compiled and analyzed using standard statistical analysis. Statistical Package for the Social Sciences (SPSS) version 20.0 and Microsoft Excel were used for the data analysis and presentation Results: Present study showed the most common cause of acute pelvic pain to be ovarian cysts in which 20.8% were hemorrhagic cysts, followed by corpus luteal cyst (14.58%) and endometrioma (12.50%). Non-gynecological case like cystitis, acute appendicitis and ureteric calculus were seen in equal number which is 10.41% each. Similar way ovarian torsion and pelvic inflammatory disease were seen in 8.33 and 4.10% respectively. In 8.33% cases no diagnosis was made. Conclusions: Ultrasound plays a crucial role in diagnosis of the acute pelvic pain in female. It helps in rapid assessment and immediate decision making for operative planning.